Modular organization of FDH: Exploring the basis of hydrolase catalysis - Reuland, Steven N. (Cold Spring Harbor Laboratory Press, 2006)
An abundant enzyme of liver cytosol, 10-formyltetrahydrofolate dehydrogenase (FDH), is an interesting example of a multidomain protein. It consists of two functionally unrelated domains, an aldehyde dehydrogenase-homologous domain and a folate-binding hydrolase domain, which are connected by an ~100-residue linker. The amino-terminal hydrolase domain of FDH (N(t)-FDH) is a homolog of formyl transferase enzymes that utilize 10-formyl-THF as a formyl donor. Interestingly, the concerted action of all three domains of FDH produces a new catalytic activity, NADP(+)-dependent oxidation of 10-formyltetrahydrofolate (10-formyl-THF) to THF and CO(2). The present studies had two objectives: First, to explore the modular organization of FDH through the production of hybrid enzymes by domain replacement with methionyl-tRNA formyltransferase (FMT), an enzyme homologous to the hydrolase domain of FDH. The second was to explore the molecular basis for the distinct catalytic mechanisms of N(t)-FDH and related 10-formyl-THF utilizing enzymes. Our studies revealed that FMT cannot substitute for the hydrolase domain of FDH in order to catalyze the dehydrogenase reaction. It is apparently due to inability of FMT to catalyze the hydrolysis of 10-formyl-THF in the absence of the cosubstrate of the transferase reaction despite the high similarity of the catalytic centers of the two enzymes. Our results further imply that Ile in place of Asn in the FDH hydrolase catalytic center is an important determinant for hydrolase catalysis as opposed to transferase catalysis.